Factors Influencing Employee Retention in the Nepalese Tourism and Hospitality Sector - Rijal, Rheet (Nepalese Journal of Hospitality and Tourism Management, 2023)
This study aimed to examine various factors of employee retention in the tourism and hospitality sector in the context of Nepal. The present research was carried out using a positivist perspective as this allows the researcher to develop the hypothesis based on the theory. Using the causal-comparative research design in the study gathered primary data from 404 employees of various demographic levels at the level of gender, age group, length of work experience, sector of work, and position in various positional capacities in various organisations connected to the selected tourism and hospitality sub-sectors using a standardised questionnaire and used. both descriptive and inferential analyses. The key findings of the study revealed a significant contribution of the impacts of age group, length of work experience, and position as the essential elements influencing staff retention in the tourism and hospitality sector. The study concluded that reward and benefits, organisational reputation and job prestige, the opportunity for career development and growth, and organisational process climate and work-life have a significant impact on staff retention.